2019
DOI: 10.3390/jcm8060873
|View full text |Cite
|
Sign up to set email alerts
|

Peroral Cholangioscopy-Guided Forceps Biopsy and Endoscopic Scraper for the Diagnosis of Indeterminate Extrahepatic Biliary Stricture

Abstract: Background: Peroral cholangioscopy (POCS) has become a widely-used technique in diagnosing indeterminate biliary strictures, enabling optical viewing of the biliary system and targeted biopsies under direct vision. The diagnostic utility of the new endoscopic scraper, Trefle®, for extrahepatic cholangiocarcinoma (ECC) has also been reported. However, the diagnostic utility of POCS-guided and Trefle®-assisted tissue acquisition for ECC has never been compared empirically. We evaluated the efficacy and safety of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 26 publications
0
11
2
Order By: Relevance
“…Some studies reported that the use of POCS can improve the diagnostic accuracy of indeterminate biliary lesions (6,12). On the other hands, the sensitivities of POCS-guided forceps biopsy for malignant biliary stricture (60.1%) and cholangiocarcinoma (66.2%) were still insufficient (8) and were similar for fluoroscopic tissue acquisition (7,15). Moreover, the sensitivity and accuracy of POCSguided forceps biopsy for indeterminate biliary lesions were lower than those of visual findings for POCS in past study (13).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported that the use of POCS can improve the diagnostic accuracy of indeterminate biliary lesions (6,12). On the other hands, the sensitivities of POCS-guided forceps biopsy for malignant biliary stricture (60.1%) and cholangiocarcinoma (66.2%) were still insufficient (8) and were similar for fluoroscopic tissue acquisition (7,15). Moreover, the sensitivity and accuracy of POCSguided forceps biopsy for indeterminate biliary lesions were lower than those of visual findings for POCS in past study (13).…”
Section: Discussionmentioning
confidence: 99%
“…An endoscopic scraper (Trefle; Piolax Medical Devices, Yokohama, Japan; Supplementary Figure S1 ) is now available [ 8 ] and has been used for the diagnosis of biliary strictures, mainly in Japan [ 9 , 10 ]. This device has unique configurations; the wire-guided system is designed to access biliary strictures over the guidewire, and three scraping loops are used specifically to obtain tissues and cell samples for histology and cytology.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies reported that the use of POCS can improve the diagnostic accuracy of indeterminate biliary lesions [6,12]. On the other hands, the sensitivities of POCS-guided forceps biopsy for malignant biliary stricture (60.1%) and cholangiocarcinoma (66.2%) were still insufficient [8] and were similar for fluoroscopic tissue acquisition [7,15]. Moreover, the sensitivity and accuracy of POCS-guided forceps biopsy for indeterminate biliary lesions were lower than those of visual findings for POCS in past study [13].…”
Section: Discussionmentioning
confidence: 99%